Indonesian marine biodiversity as a sustainable resource to support Indonesian pharmaceutical industry in ASEAN pharmaceutical market - Andika Putra Riandy; Alvionita Handayani (The International Journal of Management Science and Information Technology (IJMSIT), 2015)
Indonesian waters are known as mega-diversity resource which can produce many chemical compounds. These compounds have been identified could be a sustainable source for novel drugs, especially for the usage of pharmaceutical. Up to 2007, at least 77 new compounds are from 14 sponges and 19 new compounds are from non-sponge organisms with pharmacological potential have been identified from Indonesian waters. Unfortunately, this richness is not optimized yet. By the literature survey methods, marine culture might be one of the methods which can be developed in Indonesia to overcome the degradation hazard of marine resources. Through this method, Indonesia could be a great nation with the huge of resources for domestic and ASEAN pharmaceutical industry which can provide economic value for Indonesia and also can strengthen Indonesia in facing ASEAN pharmaceutical market.
Keywords: 650; Indonesia; Mari culture; pharmacological potential